2021
DOI: 10.3390/biomedicines9101486
|View full text |Cite
|
Sign up to set email alerts
|

Overview of Acute Ischemic Stroke Evaluation and Management

Abstract: Stroke is a major contributor to death and disability worldwide. Prior to modern therapy, post-stroke mortality was approximately 10% in the acute period, with nearly one-half of the patients developing moderate-to-severe disability. The most fundamental aspect of acute stroke management is “time is brain”. In acute ischemic stroke, the primary therapeutic goal of reperfusion therapy, including intravenous recombinant tissue plasminogen activator (IV TPA) and/or endovascular thrombectomy, is the rapid restorat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

2
29
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 49 publications
(31 citation statements)
references
References 216 publications
(278 reference statements)
2
29
0
Order By: Relevance
“…21,22 It is worth noting that subjects with posterior circulation occlusions were excluded from most of the early EVT trials, and that our study found that posterior circulation occlusions were significantly more common in males, a finding that has previously been reported. 39 This poses the question of whether sex differences in post-EVT outcomes should be compared for studies carried out before and after completion of the landmark EVT trials, either in studies using pooled data traversing this period, such as meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…21,22 It is worth noting that subjects with posterior circulation occlusions were excluded from most of the early EVT trials, and that our study found that posterior circulation occlusions were significantly more common in males, a finding that has previously been reported. 39 This poses the question of whether sex differences in post-EVT outcomes should be compared for studies carried out before and after completion of the landmark EVT trials, either in studies using pooled data traversing this period, such as meta-analyses.…”
Section: Discussionmentioning
confidence: 99%
“…Alzheimer's disease (AD) is one of the most common neurodegenerative diseases, with an estimated global prevalence of 6.2 million ( 1 ). AD has multiple clinical symptoms, including memory loss, confusion regarding time or place, decline in the ability to make decisions and judgments, aphasia, apraxia and agnosia, in addition to other symptoms, including fatigue, sleep disturbance, anxiety, depression and gastrointestinal dysfunction.…”
Section: Introductionmentioning
confidence: 99%
“…Acute ischemic stroke (AIS) is viewed as one of main causes of neurologic death worldwide. 1 , 2 In China, stroke is the third highest cause of death with mortality of approximately 1.5 million in 2018, 3 which AIS may result in permanent disability, both functionally and cognitively; meanwhile, the morbidity of AIS is continuous increasing, which causes a huge economical and humanistic burden. 4 , 5 Over the decades, great advances have made in the strategies for AIS management such as neuroprotective treatment, intravenous thrombolysis, and anticoagulation treatment, while AIS patients still suffer from elevating recurrence and increasing mortality.…”
Section: Introductionmentioning
confidence: 99%
“…Acute ischemic stroke (AIS) is viewed as one of main causes of neurologic death worldwide 1,2 . In China, stroke is the third highest cause of death with mortality of approximately 1.5 million in 2018, 3 which AIS may result in permanent disability, both functionally and cognitively; meanwhile, the morbidity of AIS is continuous increasing, which causes a huge economical and humanistic burden 4,5 .…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation